Comparison of Intravenous and Periarticular Administration of Corticosteroids in Total Knee Arthroplasty: A Prospective, Randomized Controlled Study. (17th February 2021) - Hatayama, Kazuhisa; Terauchi, Masanori; Oshima, Atsufumi; Kakiage, Hibiki; Ikeda, Keiko; Higuchi, Hiroshi
Abstract : Background: Corticosteroids are widely used in total knee arthroplasty (TKA) to relieve postoperative pain and prevent postoperative nausea. The aim of this prospective, randomized controlled study was to compare the effects of intravenous and periarticular administration of corticosteroids on pain control, prevention of postoperative nausea, and inflammation and thromboembolism markers following TKA. Methods: One hundred patients undergoing TKA were randomly allocated to either the intravenous administration or periarticular injection group. The intravenous administration group received 10 mg dexamethasone 1 hour before and 24 hours after the surgical procedure, as well as a periarticular injection placebo during the procedure. The periarticular injection group received a 40-mg injection of triamcinolone acetonide during the surgical procedure, as well as an intravenous administration placebo 1 hour before and 24 hours after the procedure. Postoperative pain scores at rest and during walking and nausea scores were recorded according to the 0-to-10 Numerical Rating Scale. Interleukin-6 (IL-6), C-reactive protein (CRP), and prothrombin fragment 1.2 (PF1.2) were measured preoperatively and postoperatively. Results: Pain scores at rest and during walking 24 hours postoperatively were significantly lower in the periarticular injection group than in the intravenous administration group. Nausea scores showed no significant difference between groups. IL-6 at 24 and 48 hours postoperatively also showed no significant difference between groups. CRP at 24 and 48 hours postoperatively was significantly lower in the intravenous administration group than in the periarticular injection group. In contrast, CRP at 1 week postoperatively was significantly higher in the intravenous administration group than in the periarticular injection group. The mean PF1.2 was significantly lower in the intravenous administration group than in the periarticular injection group at 4 hours postoperatively. Two cases of deep venous thrombosis in each group were detected with use of ultrasonographic examination. Conclusions: Periarticular injection of corticosteroids showed a better pain-control effect at 24 hours postoperatively than did intravenous administration, whereas the antiemetic effect was similar between treatments. Although intravenous administration had a better anti-thromboembolic effect than periarticular injection, the incidence of deep venous thrombosis was low in both groups. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.